Traumatic medial clavicle fracture induced by chin bar of a full-face helmet following a downhill mountainbike accident - Schmitt, Thilo; Pfalzer, Florian; Huth, Jochen; Mauch, Frieder (Sportverletzung · Sportschaden, 2020)
Downhill mountain biking is a rapidly growing sport. In our case we want to present an isolated medial clavicular fracture following a mountain bike accident with a critical review on the used protection device. A 35 year old healthy patient presented to our hospital after bike accident during downhill mountain biking in Austria with pain over his right medial clavicle. The imaging showed a multifragmentary medial clavicle fracture with an intact SC-joint. Surgical intervention was recommended. Postoperative x-rays showed an anatomic reposition and correct plate positioning. The implant was removed after 18 months without any complications. A full-face helmet with a chin bar is used to achieve better protection of the maxilla, mandible and the teeth. In a hyperflexion situation of the cervical spine, a direct contact of the chin bar with the sternum, sc-joint and the medial clavicle can occur. This impact sets the mentioned structures on a high risk of dislocation and fracture as seen in our case. This risk can be significantly reduced by the combined use of a full face helmet and a neck brace. If the injury is properly identified, positive results can be achieved by surgery.
Keywords: mountainbike; traumatic clavicle fracture; full-face helmet